Building a web-based Comprehensive School Portal System Using the CodeIgniter Framework - Munawarah, Munawarah; Nurido, Ahmad (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
With the various advantages and conveniences that the internet can provide, various fields of human activity have begun to use internet technology to help facilitate the activities they undertake. Likewise with the education sector in managing its administration. The web is one of the internet technologies that is widely used to facilitate monitoring of school activities because it can be accessed easily anywhere and at any time, from school facilities to school activities. Through the use of a web data system, problems involving redundancy of student information, insynchronization between existing information and slow production of information can be overcome. By designing an information system or web-based portal, you can increase performance effectiveness.